PERBEDAAN MENYIKAT GIGI MENGGUNAKAN BULU SIKAT SOFT DAN MEDIUM TERHADAP DEBRIS INDEKS PADA SISWA KELAS VII SMP NEGERI 4 PINELENG - Ni Made Yuliana; Anneke A.Tahulending; I Ketut Harapan; Yenny Lisbeth Siahaan (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
Dental health is one aspect of all health which is the result of interactions between physical, mental and social conditions. Physical aspects affect dental and oral health. The mental aspect of psychological readiness is psychological readiness, namely whether we want or not to maintain healthy teeth and mouth. Social aspects aspects that influence attitudes and behavior. Dental and oral health is very beneficial for children's well-being in the school environment so that children are free from toothache. This research uses a quasi-experiment method using a pre-test and post-test approach. The population in this research is class VII students of SMP Negeri 4 Pineleng, totaling 97 respondents, sampling using a random sampling technique, a population of 50 respondents. This research instrument uses a diagnostic tool set and an index debris assessment format. The data obtained were tabulated and analyzed using the Paired sample T-test statistical test. The results of the paired sample t-test showed the difference between brushing teeth using a medium bristle brush on debris. 2,064 df 24 with a p value = 0.000< ?0.05, while brushing your teeth with a soft bristle brush against debris. The index results show a mean before and after .8080, tcount 7,460> 2.064, df 24 with a p value = 0.000 <?0.05. It is concluded (H1) is acceptable. The results of the study showed that the average debris index before brushing medium bristle teeth was 1.68 and after 0.65 with a difference of 1.03, while before brushing soft bristle teeth it was 1.73 and after 0.92 with a difference of 0.81, resulting in a decrease in debris The index before and after using a medium bristle brush is greater than a soft bristle brush with a difference of 0.22.